Students’ Awareness of Cultural Differences in Classroom Communication - Munir, Fairus Suryani; Dollah, Syarifuddin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines students' awareness of cultural differences in classroom communication, focusing on verbal and nonverbal aspects. The study uses a quantitative descriptive design, and data were collected through structured questionnaires administered to elementary school teacher education students from diverse cultural backgrounds. The results of the study indicate that students have a high level of cultural awareness, particularly in recognizing variations in speaking styles, questioning patterns, gestures, facial expressions, and eye contact across cultures. The findings also indicate that students who have previous multicultural learning experiences have a higher level of awareness compared to those who do not have such experiences. These results suggest that cross-cultural experiences play an important role in shaping students' understanding of communication diversity in academic settings. Overall, this study underscores the importance of promoting intercultural awareness in university classrooms to support more effective and respectful communication. Future research is recommended to use qualitative approaches for a deeper exploration of the dynamics of intercultural interactions.